Effect of family history on the incidence of hypertension in the pre-elderly - Susniati, Susniati; Asiah, Nur (Jurnal Ilmiah Kesehatan Sandi Husada, 2025)
Introduction: Hypertension is a significant public health issue, particularly in pre-elderly populations, and can lead to various chronic diseases if not properly managed. This study aims to investigate the effect of family history on the incidence of hypertension in the pre-elderly population. Method: A quantitative research design with a case-control approach was employed, involving 42 respondents (21 cases and 21 controls). Data were collected using a questionnaire and analyzed with the Chi-square test. Results: The findings revealed a significant association between family history and the occurrence of hypertension in the pre-elderly, with a p-value of 0.000. Conversely, no significant relationship was found between physical activity and hypertension incidence (p-value = 0.634). Conclusion: The study concludes that family history is a significant risk factor for hypertension in the pre-elderly. At the same time, physical activity does not appear to influence the condition in this group. Regular monitoring and management of blood pressure, particularly for those with a family history of hypertension, are crucial for preventing the development of hypertension in the pre-elderly population